Evolution of the interfacial phases in Al2O3–Kovar® joints brazed using a Ag–Cu–Ti-based alloy. Issue 10 (3rd April 2017) - Ali, Majed; Knowles, Kevin M.; Mallinson, Phillip M.; Fernie, John A.
Abstract: A systematic investigation of the brazing of Al2 O3 to Kovar ® (Fe–29Ni–17Co wt.%) using the active braze alloy (ABA) Ag–35.25Cu–1.75Ti wt.% has been undertaken to study the chemical reactions at the interfaces of the joints. The extent to which silica-based secondary phases in the Al2 O3 participate in the reactions at the ABA/Al2 O3 interface has been clarified. Another aspect of this work has been to determine the influence of various brazing parameters, such as the peak temperature, T p, and time at T p, τ, on the resultant microstructure. As a consequence, the microstructural evolution of the joints as a function of T p and τ is discussed in some detail. The formation of a Fe2 Ti layer on the Kovar ® and its growth, along with adjacent Ni3 Ti particles in the ABA, dominate the microstructural developments at the ABA/Kovar ® interface. The presence of Kovar ® next to the ABA does not change the intrinsic chemical reactions occurring at the ABA/Al2 O3 interface. However, the extent of these reactions is limited if the purity of the Al2 O3 is high, and so it is necessary to have some silica-rich secondary phase in the Al2 O3 to facilitate the formation of a Ti3 Cu3 O layer on the Al2 O3 . Breakdown of the Ti3 Cu3 O layer, together with fracture of the Fe2 Ti layer and separation of this layer from the Kovar ®, has been avoided by brazing at temperatures close to the liquidus temperature of the ABA for short periods of time, e.g., for T p between 820 and 830 °C and τ between 2 and 8 min.